Differentiated Integration and Disintegration in the EU after Brexit: Risks versus Opportunities. (14th November 2019) - Leruth, Benjamin; Gänzle, Stefan; Trondal, Jarle
Abstract: Differentiation is becoming an increasingly salient feature of European integration. The multifaceted European crisis and the subsequent Brexit vote (paving the way for a ground‐breaking case of differentiated disintegration) have led scholars and practitioners to think about the consequences of differentiated integration. This article draws on five empirical models of differentiation experienced by countries both inside and outside the EU: the European economic area model, the Danish model of (quasi‐)permanent differentiation, the Swedish model of de facto differentiation, the instrumental model and the Brexit process of differentiation. It addresses the different risks and opportunities that each of these models entail. The article also introduces the contributions to this symposium, which aims at paving the way for future research on the consequences of differentiation in light of Brexit. Abstract : This article is part of the 2019 Symposium titled ' Responding to Brexit: Differentiated integration and disintegration in the European Union ', which also includes On the Methodology of Studying Differentiated (Dis)integration: Or How the Potential Outcome Framework Can Contribute to Evaluating the Costs and Benefits of Opting In or Out by Marian Burk and Dirk Leuffen (https://doi.org/10.1111/jcms.12958 ), The End of Exceptionalism and a Strengthening of Coherence? Law and Legal Integration in the EU Post‐Brexit by Paul James Cardwell (https://doi.org/10.1111/jcms.12959 ), Differentiated (Dis)integration in Practice: The Diplomacy of Brexit and the Low Politics of High Politics by Øyvind Svendsen and Rebecca Adler‐Nissen (https://doi.org/10.1111/jcms.12960 ) and Rethinking Britain's Role in a Differentiated Europe after Brexit: A Comparative Regionalism Perspective by Philomena Murray and Alex Brianson (https://doi.org/10.1111/jcms.12961 ).